Pharmacogenetics Overview of Quetiapine for Mental Health Disorders - Khaira, Syifa; Qolbina, Shofura Marsa; Barliana, Melisa Intan; Zakiyah, Neily (Farmaka, 2024)
Severe mental health disorders, such as schizophrenia and bipolar, often require treatment with atypical antipsychotic drugs, yet many patients exhibit incomplete responsiveness and adverse effects. This has led to the exploration of pharmacogenetics to personalize treatment potentially. Quetiapine, a commonly used atypical antipsychotic, is often used in mental health disorders for depressive episodes. Its pharmacokinetics and pharmacodynamics are potentially influenced by genetic variations in Cytochrome P450 (CYP) enzymes, Dopamine receptor D3 (DRD3), and other genes. Previous studies investigated the impact of genetic variants on quetiapine metabolism, revealing possible associations with CYP2D6, CYP2C19, Catechol-O-methyltransferase (COMT), and other genes. Notably, the COMT variant rs13306278 was linked to increased quetiapine exposure. CYP3A5 and CYP2B6 phenotypes also affected quetiapine variability, with the  ATP-binding cassette super-family G member 2 (ABCG2) variant rs2231142 associated with quetiapine accumulation. Recent pharmacogenetic advancements emphasize individualized treatment based on genetic profiles, particularly considering interactions with CYP3A4. Although concerns exist regarding drug-drug interactions and limited efficacy in certain conditions, integrating genetic information into clinical practice holds promise for optimizing quetiapine therapy and improving patient outcomes.